Predicting hypertension through big five personality traits: a four-year longitudinal study in Japan - Sixin Deng; Juan Ignacio López; Junyi Xue; Atsushi Oshio (BMC Psychology)
Abstract Objective Cardiovascular diseases (CVDs) are a leading cause of mortality worldwide, with hypertension being the most prevalent and modifiable risk factor. This study aims to examine the role of the Big Five personality traits in predicting hypertension risk in a Japanese cohort over a four-year period. Method Longitudinal data from the Human Information Database managed by NTT Data Institute of Management Consulting were analyzed. The final sample included 7,321 individuals (4,069 males, 3,252 females; mean age = 51.98, SD = 13.47). Personality traits were assessed using the Ten-Item Personality Inventory-Japanese (TIPI-J), and hypertension status was monitored annually from 2019 to 2022. A hierarchical multinomial logistic regression was employed to identify significant predictors of sustained and incident hypertension. Results Higher conscientiousness was associated with a lower risk of both sustained and incident hypertension, whereas greater openness was linked to an increased risk of sustained hypertension. In addition to personality traits, demographic factors such as age, gender, and income were significant predictors of hypertension risk. Conclusions Personality traits, particularly conscientiousness and openness, play a crucial role in hypertension outcomes. These findings suggest the importance of personalized interventions that consider both psychological and demographic factors to improve hypertension prevention and management strategies.